Ribose 5-Phosphate Isomerase B Knockdown Compromises Trypanosoma brucei Bloodstream Form Infectivity - Loureiro, Inês; Faria, Joana; Clayton, Christine; Macedo-Ribeiro, Sandra; Santarém, Nuno; Roy, Nilanjan; Cordeiro-da-Siva, Anabela; Tavares, Joana (PLOS Neglected Tropical Diseases, 2015)
Author Summary Within the non-oxidative branch of the pentose phosphate pathway, ribose 5-phosphate isomerase catalyzes the inter-conversion of ribose 5-phosphate and ribulose 5-phosphate. There are two types of ribose 5-phosphate isomerase, namely A and B. The presence of type B in Trypanosoma brucei, and its absence in humans, make this protein a promising drug target. African sleeping sickness is a serious parasitic disease that relies on limited chemotherapeutic options for control. In our study, a functional characterization of Trypanosoma brucei ribose 5-phosphate isomerase B is reported. Biochemical studies confirmed enzyme isomerase activity and its downregulation by RNAi affected mainly parasites infectivity in vivo. Overall this study shows that ribose 5-phosphate isomerase depletion is detrimental for parasites infectivity under host pressure.